THE QUALITY OF EARLY CHILDHOOD EDUCATION SERVICE IN INDONESIA - Sanny, Lim (Social Economics and Ecology International Journal, 2017)
Education is the most important thing as education  is a strategic tool to improve the standard  of human life. Parents play a very important role in choosing their children’s school. This research aims to  find  out  the  effect  of  quality  of  educational  service  and  school  reputation  to  parents’ satisfaction towards  parents’ decision  in  choosing  the  school.  Research  is  done  in  Indonesia,  taking  400  random samples from Indonesia’s big cities. The result shows that parents’ decision in choosing a school is highly affected by the service quality of educational service and school reputation. As a result, the improvement of service quality for every school is required in order to make parents more satisfied and to gain a good reputation.